A LOCAL COMMUNITY INTERNET REGISTRATION WITH NETWORK FAILURE REPORT MONITORING SYSTEM - Dedi Gunawan; Diah Priyawati; Devi Afriyantari Puspa Putri; Ihsan Cahyo Utomo; Fatah Yasin Al Irsyadi; Rusnilawati Rusnilawati; Alfian Yulianto (Informatika, Universitas Jenderal Soedirman, 2022)
Observing the great potential of the internet in rural environment, village government in Kragan, Gondangrejo District, Karanganyar Regency, has established internet network that residents could use with relatively lower price compared to that of other internet providers. Even though the internet connection has adequate speed, it still has obstacles specifically in managing the internet subscribers. Every villager who will subscribe to the internet must go to the village office and fill out a registration form and then the form is archived. Although the method is effective, it is vulnerable to customer data and information loss and is not flexible for residents who carry out their daily activities in a place that is relatively far from the village office. In addition, when there is an internet interruption, customers must send short messages to administrator, and then it will be inspected by a technician. Every reported problem is not stored properly, as a result, administrators cannot monitor whether customer complaints have been resolved. To overcome these two problems, a web-based application that is flexible and can be used by users with various computer platforms is proposed. The application development follows the waterfall model. The results of testing using black-box technique show that the functionality of the application is running with a failure percentage of 0%. Meanwhile, the test to determine usability level of the application using the System Usability Scale (SUS) method showed an acceptance rate of 66,2%, meaning that the application is suitable for use even though training for the users is needed.